PENGARUH KOMITMEN ORGANISASI, EFIKASI DIRI DAN MOTIVASI KERJA TERHADAP LOYALITAS KERJA PEGAWAI DI KANTOR PELAYANAN PAJAK PRATAMA MEDAN PETISAH - Cut Rizki Amalia (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2020)
The formulation of the problem in this research is how the influence of organizational commitment on employees work loyalty. How  influence of self efficacy on employees work loyalty. How  influence of work motivation on employees work loyalty. How  influence of organizational commitment, self efficacy and work motivation on employees work loyalty. The purpose of this research is for know influence and analize of  organizational commitment on employees work loyalty. For know influence and analize of self efficacy on employees work loyalty. For know influence and analize work motivation on employees work loyalty. For know influence and analize organizational commitment, self efficacy and work motivation on employees work loyalty.  The sample in this research is 88 employees, with data analysis technique used is multiple linear regression analyze. The results of this research explain that organizational commitment effect has a positive and significant on employee work loyalty. Self efficacy effect has a positive and significant on employee work loyalty. Work motivation effect has a positive and significant on employee work loyalty. Organizational commitment, self efficacy and work motivation effect  have a positive and significant on employee work loyalty